OP3 Cost-effectiveness of the U.S. FDA added sugar labeling policy for improving cardiometabolic health: microsimulation modelling study. (September 2018) - Kypridemos, C; Huang, Y; Liu, J; Lee, Y; Pearson-Stuttard, J; Collins, B; Bandosz, P; Capewell, S; O'Flaherty, M; Micha, R; Whitsel, L; Wilde, P; et al.
Abstract : Background: Excess added sugars, particularly from sugar-sweetened beverages (SSBs), are associated with cardiometabolic risk including type 2 diabetes (T2D) and cardiovascular disease (CVD). Despite recent declines in SSB intake in the US, added sugar intake from SSBs and foods remains high and substantially exceeds dietary recommendations. The US Food and Drug Administration (FDA) announced major changes to the Nutrition Facts panel in 2016, including mandatory labeling of added sugar content, as a strategy to target added sugars in packaged foods and beverages. However, the potential health and economic benefits of the FDA proposal remain unclear. Objective: To estimate the cardiometabolic and economic effects of implementing FDA's added sugar labeling policy from 2018–2037. Methods: We used the validated, US IMPACT Food Policy microsimulation model to estimate the T2D and CVD cases averted and quality-adjusted life-years (QALYs) gained from the FDA policy for US adults age 30–84 years. We modelled two policy scenarios: implementation of the FDA added sugar labeling policy (sugar label) anticipated reactive industry reformulation (sugar label+reformulation). Model inputs included national health statistics from CDC; added sugar intakes from NHANES; policy effects on consumer intake from labeling intervention studies; obesity-mediated and direct effects of added sugars from SSBs and other foods on T2D and CVD from meta-analyses; policy costs including government administrative costs; industry compliance costs from federal government reports; healthcare costs including medical, productivity, and indirect costs from the AHA and American Diabetes Association. All costs were inflated to constant 2017 US dollars, then discounted annually at 3%. We took a societal perspective and assumed a willingness to pay of $1 00 000 per QALY. Probabilistic sensitivity analysis accounted for model parameter uncertainty and population heterogeneity. Results: Between 2018 and 2037, the sugar label could prevent approximately 354, 400 CVD cases (95% UIs: 167, 000–673, 500) and 5 99 300 diabetes cases (302, 400–957, 400), gain some 727, 000 QALYs (401, 300–1, 138, 000), and save approximately $31 bn (15.7–54.5) in net costs from a healthcare perspective or $62 bn (33.1–103.3) from a societal perspective. For the sugar label+ reformulation  scenario, corresponding gains could be substantially larger: approximately 708, 800 CVD cases (369, 200–1, 252, 000), 1.2 m diabetes cases (0.7–1.7), and 1.3 m (0.8–1.9) QALYs, with some $58 bn (31.9–92.4) and $113 bn (67.3–175.2) net savings from the healthcare and societal perspectives respectively. Scenarios were estimated with >80% probability to be cost-saving by 2023. Conclusion: Implementing the FDA added sugar labeling policy could generate substantial health gains and cost savings for the US population.